Static localization for underwater acoustics sensor networks using Nelder–Mead algorithm for smart cities. (2nd March 2021) - Kulandaivel, Madhumitha; Natarajan, Arulanand; Chandrasekaran, Bharathi Priya; Selvaraj, Anandamurugan
Abstract: Localization is considered as an important research concept for underwater acoustic sensor networks (UASNs). It performs significant role in diverse routing methods, estimating the node position and node recovery. In UASNs, localization methods have different characteristics compared with the terrestrial networks. The challenges involved in UASNs are varying water temperature and pressure, time synchronization of beacon nodes, complicated ocean currents, and positioning of nodes. To overcome these challenges, a virtual node is deployed using the Nelder–Mead algorithm with the static localization method. In this study, two types of localization methods namely static and dynamic methods are considered and a virtual node is deployed in a static localization manner. Since anchor nodes cannot communicate to the entire network for localization additionally, virtual nodes are deployed to measure the received signal strength indicator and error ratio for effective transmission. In addition "GPS node" is equipped with a ship for easy deployment without communication overhead. The simulation result justifies that static localization for an autonomous underwater sensor networks perform with better coverage rate without time synchronization and acoustic transmission overhead.